2013
DOI: 10.1007/s00253-013-5187-0
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of the bacterial and fungal biodiversity and dynamics during Massa Medicata Fermentata fermentation

Abstract: The microbial community dynamics play an important role during Massa Medicata Fermentata (MMF) fermentation. In this study, bacterial and fungal communities were investigated based on the culture-dependent method and polymerase chain reaction-denaturing gradient gel electrophoresis analysis. Meanwhile the dynamic changes of digestive enzyme activities were also examined. Plating results showed that MMF fermentation comprised two stages: pre-fermentation stage (0–4 days) was dominated by bacterial community and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 26 publications
0
17
1
Order By: Relevance
“…This study confirmed that pathogenic bacteria exist in the traditional Chinese medicine Shenqu. The existence of pathogenic bacteria is likely to affect the quality of various batches of Shenqu compared with batches of Shenqu that have undergone pure bred fermentation22, 6 also investigated the microbial community of Shenqu by PCR-DGGE and found that the dominant microbes belonged to the genera Enterobacter , Pediococcus, Pseudomonas , Mucor , and Saccharomyces , which are results that are somewhat different from ours. This outcome is probably due to the different proportions of ingredients and fermentation parameters used in the two studies.…”
Section: Discussioncontrasting
confidence: 72%
“…This study confirmed that pathogenic bacteria exist in the traditional Chinese medicine Shenqu. The existence of pathogenic bacteria is likely to affect the quality of various batches of Shenqu compared with batches of Shenqu that have undergone pure bred fermentation22, 6 also investigated the microbial community of Shenqu by PCR-DGGE and found that the dominant microbes belonged to the genera Enterobacter , Pediococcus, Pseudomonas , Mucor , and Saccharomyces , which are results that are somewhat different from ours. This outcome is probably due to the different proportions of ingredients and fermentation parameters used in the two studies.…”
Section: Discussioncontrasting
confidence: 72%
“…For fungi, the approximate 350 bp fragment of the 18S rRNA gene was amplified using the primers NS1 (GTAGTCATATGCTTGTCTC) and GC‐Fung (CGCCCGCCGCGCCCCGCGCCCGGCCCGCCGCCCCCGCCCCATTCCCCGTTACCCGTTG) (Xu et al . ).…”
Section: Methodsmentioning
confidence: 97%
“…Total contents of soil bacteria and fungi were determined by real‐time PCR amplifications as described above. The bacteria‐specific primer set was 357f (5′‐CCTACGGGAGGCAGCAG‐3′)/517r (5′‐ATTACCGCGGCTGCTGG‐3′) and the fungi‐specific primer set was NS1 (5′‐GTAGTCATATGCTTGTCTC‐3′)/GCFung (5′‐ATTCCCCGTTACCCGTTG‐3′) …”
Section: Methodsmentioning
confidence: 99%
“…The bacteria-specific primer set was 357f (5 ′ -CCTACGGGA GGCAGCAG-3 ′ )/517r (5 ′ -ATTACCGCGGCTGCTGG-3 ′ ) 24 and the fungi-specific primer set was NS1 (5 ′ -GTAGTCATATGCTTGTCTC-3 ′ )/ GCFung (5 ′ -ATTCCCCGTTACCCGTTG-3 ′ ). 25…”
Section: Soil Microorganism Content Analysismentioning
confidence: 99%